Revolutionizing Cancer Treatment: Harnessing Cell-membrane Coated Nanoparticles for Precise Targeting and Therapy - Waghode, Pranali; Rao, G.S.N. Koteswara; Deshpande, Sanika; Budha, Roja Rani; Alavala, Rajasekhar Reddy; Kovvasu, Surya (Current Cancer Therapy Reviews, 2025)
Cancer is still a significant worldwide health issue that requires novel techniques for diagnosis and treatment. The complications associated with cancer are explored in this article, which also introduces the novel concept of biomimetic nanoparticles as potential breakthrough in the fight against the disease. The introduction gives a general review of cancer, explaining its complexity and the underlying mechanisms that give rise to it. Epidemiological findings highlight the impact of cancer on the entire world and the most extensively found cancer driving the demand for innovative therapeutic approaches. A comprehensive review of the various cancer types follows with emphasis on unique traits, diagnostic methods, and treatment modalities, highlighting the variety of difficulties. An achievable path forward for targeted cancer therapy is the emerging science of biomimetic nanoparticles. A thorough review of their many varieties and applications follows their introduction. These nanoparticles’ inventive nature, which was inspired by biological systems, is highlighted by the explanation of how they were synthesized. The focus is on biomimetic nanoparticles based on cancer cell membranes as a novel means of medication administration and targeted therapy. Their use in the treatment of cancer is being investigated, with an emphasis on their potential to improve therapeutic efficacy and lessen side effects. Particularly noteworthy are the in-depth discussions of the unique difficulties encountered in treating lung, breast, prostate, colon, colorectal, ovarian, leukemia, lymphoma, melanoma, pancreatic, bladder, oral, gastric, hepatic, perihilar cholangiocarcinoma, and cervical cancers. The article also mentions the various challenges which may occur during this entire process.
Keywords: Cancer